ANALISIS PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN DI WARUNG GOCENG DEPOK: STUDI KASUS (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
This research was conducted due to the challenges faced by Warung Goceng in Depok, such as inconsistent product quality, price competition, and customer service issues, which motivated this study. The aim of this study is to evaluate the influence of price on customer purchasing decisions. Using a quantitative approach, 60 customers of Warung Goceng in Depok City participated as research participants. Data were obtained through the distribution of questionnaires and observation, and hypothesis testing was conducted using SPSS. The findings of the study indicate that the majority of consumer purchasing decisions are significantly influenced by price factors, and there is a direct relationship between Warung Goceng's prices and consumer purchasing decisions Bonus dan promosi menarik adalah salah satu daya tarik utama Indohoki77. Platform ini menawarkan berbagai jenis bonus seperti bonus selamat datang, bonus deposit, dan cashback . Therefore, Warung Goceng can improve its pricing strategy to better suit consumer preferences and enhance its competitiveness in the culinary industry
Keywords: analysis; harga; keputusan pembelian; pemasaran